Electromagnetohydrodynamic flow transport of two layer fluids through a microchannel with interfacial slip at fluid-solid interface. Issue 1 (March 2021) - Rana, Amalendu; Mishra, Dwaipayan; Reza, Motahar; Mondal, Himadri Shekhar
Abstract: This work investigates an electromagnetohydrodynamic flow of two layer fluids through a microchannel under the influence of interfacial slip at fluid-solid interface. The governing equations of conservation of momentum and potential distribution equations with Debye-Huckel approximation has been simplified analytically. The effects of different parameters like transverse electric field, viscosity ratio, interfacial charge density has been presented graphically. Also this study explored that the effect of Hartmann number and large Hartmann number on the velocity of fluid are almost opposite. These results are valid to the available data. Also it is shown that the interfacial charge density has a crucial role to play with the velocity of a fluid.